2018
DOI: 10.1186/s13058-018-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging and molecular features associated with tumor-infiltrating lymphocytes in breast cancer

Abstract: BackgroundWe sought to investigate associations between dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) features and tumor-infiltrating lymphocytes (TILs) in breast cancer, as well as to study if MRI features are complementary to molecular markers of TILs.MethodsIn this retrospective study, we extracted 17 computational DCE-MRI features to characterize tumor and parenchyma in The Cancer Genome Atlas cohort (n = 126). The percentage of stromal TILs was evaluated on H&E-stained histological whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…Others have reported high lymphocytic infiltration to be associated with texture entropy features, 69 qualitative tumor enhancement profile and margin appearance in TN tumors, 70 and background parenchymal enhancement within 20 mm from the tumor. 71 Associations between intratumoral 72 and peritumoral 73 textural heterogeneity features with immune response at the molecular and morphometric scale have also been reported in the context of lung computed tomography. Recently, Chen et al 74 found that incorporating peritumoral radiomic analysis of hepatocellular cancer on contrast-enhanced MRI significantly improved the capability to estimate the immunoscore of TIL density and arrangement compared with a model containing only intratumoral features.…”
Section: Discussionmentioning
confidence: 83%
“…Others have reported high lymphocytic infiltration to be associated with texture entropy features, 69 qualitative tumor enhancement profile and margin appearance in TN tumors, 70 and background parenchymal enhancement within 20 mm from the tumor. 71 Associations between intratumoral 72 and peritumoral 73 textural heterogeneity features with immune response at the molecular and morphometric scale have also been reported in the context of lung computed tomography. Recently, Chen et al 74 found that incorporating peritumoral radiomic analysis of hepatocellular cancer on contrast-enhanced MRI significantly improved the capability to estimate the immunoscore of TIL density and arrangement compared with a model containing only intratumoral features.…”
Section: Discussionmentioning
confidence: 83%
“…Wu et al. extracted 17 computational DCE-MRI features and showed significant association with TIL levels in breast cancer (30). In this study, four imaging features were significantly associated with TILS, including tumor volume, cluster shade of signal enhancement ratio (SER), mean SER of tumor-surrounding BPE, and proportion of BPE.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI data were normalized and resized 63 . Specifically, pixel values were normalized by the mean of the interquartile values of the gland tissue in the precontrast MR image, ensuring that the signals inside the tumour and from the parenchymal region were normalized comparably.…”
Section: Methodsmentioning
confidence: 99%